Impact of inflation on financial statement - Pushkareva, Mary; Nikitenko, Olga (My University, 2015)
Domestic and foreign experience shows the dependence of the results of accounting from such economic factors as inflation. The need of coverage of this aspect of accounting in Ukraine is primarily due to significant price changes in the economy of our state. Inflation accounting, a range of accounting systems designed to correct problems arising from historical cost accounting in the presence of inflation, is a solution to these problems.
Keywords: облік за первинною собівартістю; рентабельність; фінансова звітність; інфляція; учет по себестоимости; рентабельность; финансовая отчетность; инфляция; historical cost accounting; profitability; financial statements; inflation; кафедра ділової іноземної мови та міжнародної комунікації